A Dance Work "Kaweng" Visualization Of Sarong Property Tengger Community In Dramatic Dance Work: Karya Tari "Kaweng" Visualisasi Properti Sarung Pada Masyarakat Tengger Dalam Bentuk Tari Dramatik - Sandria, Fella Aulia Sandria Hakim; Sasanadjati, Jajuk Dwi (Solah, 2025)
Kaweng dance work departs from one of the traditions of the Tengger people, namely the use of sarong as the main weapon to fight the cold of the Mount Bromo area. The sarong is used by both women and men, but the sarong used by women has its own meaning in each knot or tie on the shoulder, if the knot or tie of the sarong is at the back then the woman is a sign of being married, then the knot in front indicates a pregnant woman, and the last knot is on the right or left shoulder indicating that the woman is still a girl or unmarried. Meanwhile, the sarong used by men does not have a meaning in each tie or knot. There are two focuses in this dance work, namely the focus of content that describes the use of sarongs by women, especially teenagers, in daily activities that have been applied from generation to generation that must be preserved so as not to fade, and the focus of the form of this dance work is worked on with a dramatic type. The creation method used for this choreographic process uses Jacqueline Smith's Construction Method I starting from initial stimulation, improvisation, evaluation, selection and refinement, and motifs. Then there are other supporting elements such as musical accompaniment, props, makeup and clothing, and stage techniques in accordance with the theme needed.